Abdullah b. Rawahah - as an embodiment of heavenly justice - Omer, Spahic (AboutIslam, 2019)
Abdullah b. Rawahah was a leading companion of Prophet Muhammad (peace and blessings be upon him). He was from the rank of Ansar (the Helpers, or the local inhabitants of Madinah). Moreover, he was a scribe and poet. During the battle of Mu’tah in the 8th year after Hijrah against the forces of the Byzantine Empire, he was third in command. He was killed in the same battle. After the battle of Khaybar in the 7th year after Hijrah against the renegade Jews, the Jews were defeated and an agreement was signed. According to the agreement, the Jews were allowed to remain on their lands and in their fortresses, while obliging them to pay half their agricultural yield to the Prophet’s state. The Prophet (peace and blessings be upon him) then appointed Abdullah b. Rawahah to estimate the agricultural produce of the Jews and to make sure that the taxes were duly paid, as per the agreement.